A comprehensive review of farmers producer organizations in India: Historical evolution, current status and future policy challenges - Yazhini, A; Malaisamy, A; Rani, S P; Ramakrishnan, K; Prabakaran, K; Arunachalam, P (Plant Science Today, 2025)
Agriculture plays an important role in India but faces various challenges. A large number of farmers in India have small and marginal holdings of less than two hectares, which is linked to the increasing fragmentation of land. Many institutional policies aim to improve the farmer’s livelihoods to mitigate the disadvantages of land fragmentation. These measures include the formation of Primary Agricultural Cooperative Society (PACS), Self-Help Group (SHG), Joint Liability Group (JLG) and Common Interest Group (CIG). However, there are limitations to these initiatives, as they often provide considerably more managerial control and influence to local powerful individual. In response, Farmers Producer Organizations (FPOs) have emerged as pivotal entities aimed at integrating smallholders into mainstream markets. India has over 10,000 FPOs, benefiting 4 million farmers and increasing income by 20-25%. But 70% face sustainability challenges. Policy initiatives, such as NABARD’s Rs.6,865 crore schemes, an aim to address these issues. This paper considered the Scopus database using the Boolean keyword "Farmer" AND "Producer organization" and identified articles were shortlisted after screening using PRISMA framework. While previous studies have offered insights into various aspects of FPOs, there remains a significant lack of cohesive analysis integrating historical trends, current challenges and future policy directions. This study identifies key factors influencing FPO system, including governance mechanisms, market linkages and capacity-building initiatives. The review highlights current challenges and opportunities within the FPO system, suggesting policy recommendations for future development. The findings offer valuable insights into the transformative potential of FPOs and inform strategic policy recommendations to ensure their sustainability in India's agricultural sector.